The Routledge companion to feminist philosophy - Garry, Ann; Khader, Serene J.; Stone, Alison (Routledge, 2017)
"The Routledge Companion to Feminist Philosophy is an outstanding guide and reference source to the key topics, subjects, thinkers, and debates in feminist philosophy. Fifty-six chapters, written by an international team of contributors specifically for the Companion, are organized into five sections: (1) Engaging the Past; (2) Mind, Body, and World; (3) Knowledge, Language, and Science; (4) Intersections; (5) Ethics, Politics, and Aesthetics. The volume provides a mutually enriching representation of the several philosophical traditions that contribute to feminist philosophy. It also foregrounds issues of global concern and scope; shows how feminist theory meshes with rich theoretical approaches that start from transgender identities, race and ethnicity, sexuality, disabilities, and other axes of identity and oppression; and highlights the interdisciplinarity of feminist philosophy and the ways that it both critiques and contributes to the whole range of subfields within philosophy."–The publisher.
Le chapitre 22 de Miranda Fricker et Katharine Jenkins, “Epistemic injustice, ignorance, and trans experiences” a été donné en lecture au cours FEM9000.
Keywords: afro-féminisme; approches et analyses; autonomie; bioéthique; care; cours; cycles supérieurs; discipline; environnement; esthétique; fem9000; féminisme africain; féminisme autochtone; féminisme décolonial; féminismes noirs; identité; injustices épistémiques; intersectionnalité; justice sociale; matérialité; objectivité; outils; ouvrages de références; philosophie; philosophie féministe; phénoménologie; politique de genre; queer; rationnalité; religion; sciences humaines; subjectivité; thématiques; théorie du contrat social; transféminisme; écologie; éthique; éthique du care; études critiques de la race; études critiques du handicap

Les rabat-joie féministes (et autres sujets obstinés) - Ahmed, Sara (Cahiers du Genre, 2012)
Interrogeant la figure de la « féministe rabat-joie », cet article propose d’en explorer la négativité, aussi bien que la capacité d’agir dont elle est la promesse. Il s’agit ainsi, en repositionnant la pensée féministe comme critique de l’injonction au bonheur, de comprendre le sujet féministe en tant que sujet obstiné. L’obstination féministe est alors appréhendée comme le socle incertain d’une politique collective traduisant les émotions individuelles, la douleur ou la colère ressentie face aux injustices. Au-delà, la figure du sujet obstiné permet de saisir la façon dont, au sein des espaces féministes, les femmes noires ont pu être réduites à leur colère et désignées comme cause des divisions engendrées par le racisme. La position de sujet obstiné constituerait ainsi autant un lieu de tensions que de revendications politiques. https://www.saranahmed.com/
Keywords: 1900-1999; afro-féminisme; amériques; antiracisme; approches et analyses; care; cours; discipline; europe; fem1000; féminismes noirs; incontournable; intersectionnalité; luttes; militance; occident; orient; philosophie; phénoménologie; politique; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles